Low back pain - Ehrlich George E. (The World Health Organization, 2003)
Low back pain is a leading cause of disability. It occurs in similar proportions in all cultures, interferes with quality of life and work performance, and is the most common reason for medical consultations. Few cases of back pain are due to specific causes; most cases are non-specific. Acute back pain is the most common presentation and is usually self-limiting, lasting less than three months regardless of treatment. Chronic back pain is a more difficult problem, which often has strong psychological overlay: work dissatisfaction, boredom, and a generous compensation system contribute to it. Among the diagnoses offered for chronic pain is fibromyalgia, an urban condition (the diagnosis is not made in rural settings) that does not differ materially from other instances of widespread chronic pain. Although disc protrusions detected on X-ray are often blamed, they rarely are responsible for the pain, and surgery is seldom successful at alleviating it. No single treatment is superior to others; patients prefer manipulative therapy, but studies have not demonstrated that it has any superiority over others. A WHO Advisory Panel has defined common outcome measures to be used to judge the efficacy of treatments for studies.